STRATEGI KOMUNIKASI PENINGKATAN ENGAGEMENT (LIKE, SHARE, DAN COMMENT) TIKTOK @UNIVERSITAS DIPONEGORO DAN INSTAGRAM @UNDIP.OFFICIAL MELALUI PRODUKSI KONTEN VIDEO SEBAGAI DATA EXECUTIVE DAN COPYWRITER - Duan Karunia Deswan; Agus Naryoso (Interaksi Online, 2026)
Along with the rapid development of information technology, Diponegoro University(UNDIP) actively utilizes digital communication channels as a strategic tool to strengthen itsinstitutional image and reputation. As a higher education institution targeting Generation Z,UNDIP faces challenges in creating effective interactions through social media, particularlyon the TikTok platform. Content delivery that tends to be overly formal and one-directionaloften fails to capture the interest of younger audiences who prefer a more human-centered,inclusive, and interactive communication approach. This project aims to design and implementa communication strategy through the program “Jejak UNDIP” to increase engagement levelssuch as likes, shares, and comments on the TikTok account @undip.official. Throughsystematically produced video content, the project focuses on several content pillars, includinghighlighting the human side of campus life, introducing facilities such as Electric Buggythrough the Smart & Eco Campus campaign, and showcasing student achievements. Theimplementation results indicate that shifting the communication style from a formal andsegmentative approach to a more interactive one has proven effective in significantly increasingaudience participation. This rise in engagement not only expands the reach of informationdissemination but also strengthens UNDIP’s image as a modern, adaptive, and relevantuniversity for Generation Z.